Odpowiedzi

Najlepsza Odpowiedź!
2010-04-11T16:59:04+02:00
) P=d/mRT obustronnie razy mRT
PmRT=d /PRT
m=d/PRT

b) nie wiem o co ci chodzi w tym b xD

c) s= vt+at/2 obustronnie razy 2
2s=vt+at
2s=t(v+a) / t
2s/t=v+a
a=2s/t-v
wspolny mianownik
a=2s/t -vt/t
a=2svt/t

d) F=GMn/r *r
Fr=GMn/Gn
Fr/Gn=M


59

a) t=x/a-5x razy (a-5x)
t(a-5x)=x
ta-5xt=x
x+5xt=ta
x(1+5t)=ta /(1+5t)
x=ta/1+5t

b) p=a+x+ax
p-a=x+ax
p-a=x(1+a) /(1+a)
x= p-a/1+a

c) m=(x+1)p-3x /p
m/p=x+1-3x
m/p-1=x-3x
wspolny mianownik
m-p/p=-2x /-2
x=-(m-p/2p)

d) w=1x+p
w=x+p
w-p=x